The Influence Of Influencer Marketing And Product Placement On Teh Botol Sosro’s Brand Awareness - Wibowo, Aldrian; Herawaty, Tetty; Fordian, Dian (SEIKO : Journal of Management & Business, 2022)
The Fast Moving Consumer Goods (FMCG) industry, especially the ready-to-drink packaged tea beverage industry, has experienced development from year to year. The development of this industry is marked by an increase in consumption volume and also the number of brands competing in this industry. One of the competing brands in this market is Teh Botol Sosro. Teh Botol Sosro, which competes fiercely with other brands, is making various efforts to increase brand awareness amidst this intense competition. The efforts made by Teh Botol Sosro are using influencer marketing by choosing Nex Carlos as its partner, as well as implementing promotions through product placement on Nex Carlos content that was uploaded on various platforms. This research aims to determine the influence of influencer marketing and product placement on brand awareness of Teh Botol Sosro. The object of this research is influencer marketing and product placement as dependent variables. The sampling technique used in this research is non-probability sampling, namely purposive sampling. The sample in this study consisted of 100 respondents with the criteria being that they had watched Nex Carlos content which included the Teh Botol Sosro product on the content. This research uses multiple linear regression analysis. The results of this research reveal that there is an influence between influencer marketing and product placement on brand awareness, both simultaneously and partially.